Cognitive training and neuroplasticity in mild cognitive impairment (COG-IT): protocol for a two-site, blinded, randomised, controlled treatment trial - Jessica D'Antonio; Laura Simon-Pearson; Terry Goldberg; Joel R Sneed; Sara Rushia; Nancy Kerner; Howard Andrews; Caroline Hellegers; Sierra Tolbert; Elena Perea; Jeffrey Petrella; Murali Doraiswamy; et al. (BMJ Open, 2019)
Introduction Mild cognitive impairment (MCI) is common in older adults and represents a high-risk group for progression to Alzheimer’s disease (AD). Medication trials in MCI have generally failed, but new discoveries with brain plasticity in ageing have led to the study of cognitive training as a potential treatment to improve cognitive abilities. Computerised cognitive training (CCT) involves computerised cognitive exercises that target specific cognitive abilities and neural networks to potentially improve cognitive functioning through neuroplasticity.Methods and analysis In a two-site study (New York State Psychiatric Institute/Columbia University Medical Center and Duke University Medical Center), we will randomise 100 patients with MCI (Wechsler Memory Scale-III Logical Memory II score 0–11; Folstein Mini Mental State Examination ≥23) to home-based CCT (suite of exercises: memory, matching, spatial recognition, processing speed) or a home-based active control condition (computerised crossword puzzle training (CPT)) with 12 weeks of intensive training followed by regular booster sessions up to 78 weeks. All patients will receive standard neuropsychological and functional assessments in clinic as well as structural/functional brain MRI scans at study entry and endpoint. We will test if CCT, versus CPT, leads to improved cognitive functioning, transfers to functional ability and tasks of everyday life and impacts hippocampal volume changes and changes in the default mode network of the brain measured by resting-state functional MRI.Ethics and dissemination The study will be conducted following ethics approval and written informed consent will be obtained from all subjects. Study results will be disseminated via publication, clinicaltrials.gov, media and conference presentations. This will be the first controlled long-term trial to evaluate the effects of home-based CCT versus computerised CPT on cognitive abilities and functional measures and neural outcomes as determined by MRI indices in patients with MCI. Positive results from trial may support further development of home-based CCT.Trial registration number ClinicalTrials.gov identifier (NCT03205709).